Building Envelope Over-Cladding: Impact on Energy Balance and Microclimate - David Dernie; Jacopo Gaspari (Buildings, 2015)
A considerable part of recent EU policies is currently addressed at developing effective measures to support the transition towards a low carbon society according to the principles and goals of Roadmap to 2050. In this general framework the links between the development of low-emission strategies and climate-resilient approaches to buildings play a key role. As most part of the existing building stock was built before the 1980s, retrofit and renovation actions are widely investigated. Despite progress in this field, relatively little attention has been given to the connections between the achievable energy savings and the energy investment needed to pursue the renovation process and to how technological choices can impact on the energy balance according to a multi-criteria perspective. The paper will explore how different technologies and design solutions to building envelopes cladding contribute to the reduction of the heat gains in urban environments and how appropriate adaptive strategies can further mitigate against accelerated greenhouse emissions. It will discuss the relationship between individual building performance and consequent effect on external environment. The effects of technological and material choices are evaluated for some design scenarios and conditions in order to develop an indicative impact mode.